KINERJA SAMBUNGAN BOLTED STIFFENED EXTENDED END-PLATE (BSEEP) MENGGUNAKAN T-STIFFENER - Bryant Rizwantuana; Aniendhita Rizki Amalia; Budi Suswanto (Construction and Material Journal, 2026)
One of the crucial aspects in the design of earthquake-resistant buildings, especially those using steel structural systems, is the design of beam-to-column connections in the steel structure. Following the Northridge earthquake, regulations and standards for earthquake-resistant building design have been continuously developed and updated until now. This research will combine the Bolted Stiffened Extended End-Plate (BSEEP) connection from previous experimental studies with a T-Stiffener as a replacement for its stiffener plate. The T-Stiffener is made in several variations to investigate its effect when applied to a connection. This research uses ANSYS Workbench software. The connection modification modeling is planned with 6 modification models. Model-1 is the initial connection that is equated with previous experimental research. Model-2 uses the same type of stiffener as Model-1 but with the addition of a continuity plate. Model-3 and Model-4 are modification models using a T-Stiffener with a vertical height of 140 mm and lengths of 120 mm and 300 mm, which are welded to the beam flange and column flange. Model-5 and Model-6 are variations of Model-3 and Model-4 with a height of 180 mm and lengths of 120 mm and 300 mm. Model-6 produced the highest moment capacity at 4% rotation, which is 376.36 kN-m, or an increase of 27.91% from Model-1. In terms of energy dissipation, Model-6 also had the largest energy dissipation, which is 2,763.39 kN-m-rad, or an increase of 18.45% from Model-1. All analyzed connection models show relatively similar stress contours and buckling in the panel zone. This can occur because the column and beam profile sizes are relatively similar. With these relatively similar profile sizes, the connection cannot achieve a strong-column weak-beam system even though modifications have been made to strengthen the connection.